Differences in PfEMP1s recognized by antibodies from patients with uncomplicated or severe malaria. (December 2016) - Duffy, Michael; Noviyanti, Rintis; Tsuboi, Takafumi; Feng, Zhi-Ping; Trianty, Leily; Sebayang, Boni; Takashima, Eizo; Sumardy, Fransisca; Lampah, Daniel; Turner, Louise; Lavstsen, Thomas; Fowkes, Freya; et al.
Abstract Background Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) variants are encoded byvar genes and mediate pathogenic cytoadhesion and antigenic variation in malaria. PfEMP1s can be broadly divided into three principal groups (A, B and C) and they contain conserved arrangements of functional domains called domain cassettes. Despite their tremendous diversity there is compelling evidence that a restricted subset of PfEMP1s is expressed in severe disease. In this study antibodies from patients with severe and uncomplicated malaria were compared for differences in reactivity with a range of PfEMP1s to determine whether antibodies to particular PfEMP1 domains were associated with severe or uncomplicated malaria. Methods Parts of expressedvar genes in a severe malaria patient were identified by RNAseq and several of these partial PfEMP1 domains were expressed together with others from laboratory isolates. Antibodies from Papuan patients to these parts of multiple PfEMP1 proteins were measured. Results Patients with uncomplicated malaria were more likely to have antibodies that recognized PfEMP1 of Group C type and recognized a broader repertoire of group A and B PfEMP1s than patients with severe malaria. Conclusion These data suggest that exposure to a broad range of group A and B PfEMP1s is associated with protection from severe disease in Papua, Indonesia.